The Effect of Xylitol Chewing Gum on The Growth of Streptococcus Mutans Bacteria Colonial Growth in Saliva - Ni Nyoman Gemini Sari; Ni Putu Widani Astuti; Ni Komang Alisya (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: The unkempt state of the mouth and teeth can lead to the development of bacteria that cause problems in the oral cavity. Streptococcus mutans, an acid-producing bacterium, can cause caries whose numbers can be reduced by chewing Xylitol gum. Xylitol is a non-acidogenic and non-cariogenic natural sweetener that can stimulate salivary flow and increase the pH value of saliva. These bacteria cannot ferment Xylitol so acid is not produced and salivary pH does not decrease. Materials and Methods: The tools and materials used in this study were Xylitol fresh mint gum, diagnostic tools, laboratory tools, Streptococcus mutans bacteria, saliva before and after treatment. The research method used was descriptive pseudo-experimental with One Group Pre-test and Post-test design. Results and Discussion: The results of the study were analyzed with the Wilcoxon Signed Rank Test. The group between before and after treatment showed a difference in the number of bacterial colonies of 0.000, so there was a significant difference in the number of colonies in this study, with an average colony of Streptococcus mutans before treatment of 99.87 CPU/ml. While for Streptococcus mutans colonies after treatment amounted to 36.75 CPU/ml. Conclusion: From the results of the study, it can be concluded that Xylitol gum has an effect on the growth of the number of colonies of Streptococcus mutans bacteria in saliva.